2017
DOI: 10.1002/jbt.21888
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐577 suppresses tumor growth and enhances chemosensitivity in colorectal cancer

Abstract: In this work, we aimed to determine the expression and biological functions of microRNA (miR)-577 in colorectal cancer (CRC). The results showed that miR-577 was downregulated in CRC specimens and cell lines. Restoration of miR-577 significantly suppressed the proliferation and colony formation and induced a G0/G1 cell cycle arrest in CRC cells. 5-Fluorouracil (5-FU)-resistant SW480 cells (SW480/5-FU) were found to have elevated levels of miR-577. Ectopic expression of miR-577 enhanced 5-FU sensitivity in SW48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…Moreover, one study suggested that miR‐577 is downregulated in colorectal cancer specimens and cells. Restoration of miR‐577 significantly suppresses proliferation and induces a G0/G1 cell cycle arrest in colorectal cancer cells . The relative expression of miR‐577 is lower in hepatocellular carcinoma tissues than in ANT.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, one study suggested that miR‐577 is downregulated in colorectal cancer specimens and cells. Restoration of miR‐577 significantly suppresses proliferation and induces a G0/G1 cell cycle arrest in colorectal cancer cells . The relative expression of miR‐577 is lower in hepatocellular carcinoma tissues than in ANT.…”
Section: Discussionmentioning
confidence: 98%
“…Increasing evidence indicated that abnormal miRNA expression contributes to the carcinogenesis and progression of multiple human cancers (26)(27)(28). Numerous studies have shed light on tumour-targeting therapies using miRNAs as novel diagnostic and therapeutic tools (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has revealed the role of HSP27 in 5-FU resistance in colon cancer cells (15)(16)(17)(18)(19)(20). Increased expression of HSP27 resulted in greater resistance to 5-FU in colon cancer cells (18,39), whereas suppression of HSP27 via gene knockdown (16,38) or pharmaceuticals (39,40), enhanced sensitivity to 5-FU. Moreover, HSP27 is associated with VCR resistance in cancer cells (41).…”
Section: Discussionmentioning
confidence: 99%